The Role of Work Motivation as A Mediating Influence of Work Environment and Islamic Work Discipline on Lecturer Performance - Mohamad Lutfi; Koesmawan Koesmawan; Andry Priharta; Oneng Nurul Bariyah; Masyitoh Masyitoh (Asian Social Work Journal, 2023)
This study aims to determine the role of work motivation as a mediating influence of work environment and Islamic work discipline on lecturer performance in the era of disruption. The study location is PTMA in the Jakarta and Banten areas. The research method uses a quantitative approach of survey type and is associative or explanatory. The population in this study was lecturers totaling 1,838 lecturers, using the Slovin formula, a sample of 170 people was obtained using the purposive sampling technique. Data collection techniques used questionnaires and data analysis used SEM Smart PLS 3.2.9 analysis. The results of the study are known: (1) Work environment has a significant effect on Work Motivation at PTMA Jakarta Banten in the disruption era, (2) Work Discipline has a significant effect on Work Motivation at PTMA Jakarta Banten in the disruption era, (3) Work Motivation has a significant effect on Lecturer Performance at PTMA Jakarta Banten in the disruption era, (4) The role of Work Environment has a significant effect on Lecturer Performance at PTMA Jakarta Banten in the disruption era, (5) Work Discipline has a significant effect on Lecturer Performance at PTMA Jakarta Banten in the disruption era, (6) The Role of the Work Environment has a significant effect on Lecturer Performance mediated by Work Motivation at PTMA Jakarta Banten, (7) Work Discipline has a significant effect on Lecturer Performance mediated by Work Motivation at PTMA Jakarta Banten. This study implies that the role of work motivation as a mediating influence of the work environment and Islamic work discipline contributes positively to lecturer performance. The suggestion of this study is to pay attention to lecturer honoraria to be more tailored to the educational background, academic rank, and length of work of lecturers. Work facilities and equipment are expected to be more tailored to the needs of lecturers to support teaching activities. Further, improves security and comfort in learning activities. Class conditions that are not conducive in the future can create a conducive learning atmosphere so that learning activities run more effectively.